Teori Van Hiele dan Hasil Belajar dalam Bidang Geometri - Ayuni Kemala Safira (Departemen Matematika, 2019)
Geometry is one branch of mathematics that is close to student life, but in reality student geometry learning outcomes are still relatively low. Geometry learning based on the Van Hiele theory is solutions than can help students understand to be better the geometry consept. The purpose of study was to know student geometry learning outcomes who studied with learning based on the Van Hiele theory. The type of research was a quasy experiment with static group design. This research was conducted on class VIII. Sampling was done by using simple random sampling. Data in this research was final test in essay form test which consisted of 6 question, where each question contains indicator of achievement of geometry learning outcomes. The research hypothesis was proven by t test. Based on the result of data analysysis it is obtained , so it can be cocluded that student geometry learning outcomes who studies with Van Hiele theory is better than than those who learns with conventional learningKeywords — geometry learning outcomes, Van Hiele theory, conventional learning.